Pengaruh Sudut Anyam Komposit Berpenguat Serat Pelepah Pisang dengan Matriks Unsaturated Polyester - Ardhi Harist Hirosana; Sri Hastuti; R. Faiz Listyanda (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The use of lightweight plastic materials is widely applied in the manufacturing of car dashboards. Lightweight plastics or polymers, such as ABS plastic, are not strong enough or can easily crack when impacted. Banana pseudostem fibers have good mechanical properties and are a potential reinforcement for composites. This study aims to analyze the tensile strength of unsaturated polyester-banana pseudostem fiber composites produced through the hand lay-up method at three different angles: 0°/90°, 15°/105°, and 30°/120°. The tensile testing refers to ASTM D638 standards. The results of the tensile tests show that the 0°/90° weaving angle variation had the highest tensile strength value, which was 372.07 MPa. The 30°/120° fiber orientation variation had the lowest tensile strength value at 198.12 MPa. The fractures from the tensile tests were observed through macro photos to understand the failure mode. The macro photo observations showed that all specimens experienced fiber pull-out.